1999
DOI: 10.1111/j.1600-0579.1999.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the IT skills and attitudes of final year dental students at Bristol University in 1996 and 1997

Abstract: Surveys of final year dental students were conducted in 1996 and 1997 to see if there were any detectable differences in students' perception of their own information technology IT skills and attitudes towards information technology following the opening of a dedicated computer-assisted-learning (CAL) room. An increase was seen in students' confidence levels, with fewer assessing themselves as IT "beginners" (1996 = 36%; 1997 = 14%), and more assessing themselves as competent in some basic skills (52%; 41%). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 12 publications
1
33
0
4
Order By: Relevance
“…The fact that 94.9% of the medical and dental students (psva) in our survey assess their computer knowledge as sufficient or better confirms that the great majority are well equipped to use the modern media. However, it has to be taken into consideration that “normal” students tend to overestimate their computer skills, whereas experts assess their competence more strictly (Grigg and Stephens, 1999; Mattheos et al, 2002). Feldman (1992) reports that 62% of dental students at Newark, New Jersey, used word processing systems in 1991, while these obviously sufficient computer skills were described as 87% in 1993.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that 94.9% of the medical and dental students (psva) in our survey assess their computer knowledge as sufficient or better confirms that the great majority are well equipped to use the modern media. However, it has to be taken into consideration that “normal” students tend to overestimate their computer skills, whereas experts assess their competence more strictly (Grigg and Stephens, 1999; Mattheos et al, 2002). Feldman (1992) reports that 62% of dental students at Newark, New Jersey, used word processing systems in 1991, while these obviously sufficient computer skills were described as 87% in 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Computer skills of medical students at the University of Chicago were reported as being 91/92% sufficient in 1996/1997 (Hollander, 1999), whereas results of a 1996 survey of British dental students show that only 77 psva assessed themselves as competent in some basic computer skills or as unable/beginners. In a survey made after a computer‐assisted learning room was opened at this university in 1997, 66.7 psva still placed themselves in the latter group (Grigg and Stephens, 1999), while in 1997/1998, 51.1 psva of a university dental school in Ireland considered their expertise with computers as poor (Ray and Hannigan, 1999). The analysis of a decade of data collection at a U.S. medical school confirms the students' increasing computer skills over the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights one of the main barriers to using CAL in education, ie students who cannot use computers will be seriously disadvantaged. In 1996 and 1997, Bristol dental school obtained opinions from their students on the use of IT in the undergraduate curriculum 3 and the main complaint from students was the lack of adequate training in IT.…”
Section: Students' Attitudes To Ecoursementioning
confidence: 99%
“…Originally, web-based technology had limitations regarding the transmission of large multimedia files, but this may be overcome with the increased availability of high-speed internet connections. 2 Studies have shown that students consider using computers in the dental curriculum as an effective tool, 1,3,4 as CAL offers many advantages over traditional methods of learning. For example, CAL allows students to work in their own time and pace.…”
mentioning
confidence: 99%